Interpreting Performance Information: Motivated Reasoning or Unbiased Comprehension. (18th June 2015) - Baekgaard, Martin; Serritzlew, Søren
Abstract: A main rationale of performance information is to empower citizens to make informed decisions by presenting them with unambiguous information about the performance of institutions. However, even objective, clear, and unambiguous performance information is subject to biased interpretation depending on whether the information is consistent with the prior beliefs held by those who receive the information. Integrating the theory of motivated reasoning with the literature on performance information, the authors hypothesize that performance information that is inconsistent with prior beliefs is less likely to be interpreted correctly than belief‐consistent information. Using randomized survey experiments in which respondents were presented with quantitative performance data, the authors show that subjects systematically interpret performance information in ways that conform with their prior beliefs. The findings question the assumption that providing performance information automatically increases knowledge about government performance, let alone improves political decisions.